Text mining for Thai news online analysis - Chotirat, Saranlita (2013)
In current, Online social that are many information resources on computer network which many format, resource and contents are variety.Online news is one type that present facts including person, events,location, time and context to let people know the current situation early that have effect to many people in society.Nowadays, a number of Thai news online is increasing because the internet infrastructure is powerful and support requirement to access are appropriately, conveniently and quickly.This article apply to text mining technique for analysis the relationship between keywords and terms that define to data refer to person, events, location, time and discovery knowledge from amounts Thai news online.Including text mining process for Thai news online analysis and the limitations of analysis for article or text which are Thai language by using text mining.